Entrepreneurs' thriving after venture distress: The role of self-compassion, learning, and venture failure - Karlien Coppens; Mirjam Knockaert (BRQ Business Research Quarterly, 2025)
Well-being is important to entrepreneurs, yet entrepreneurship does not necessarily foster well-being. Stressful work conditions such as venture distress might put entrepreneurs' well-being under pressure. Drawing upon self-determination theory, we investigate the conditions that enhance entrepreneurs' thriving after experiencing venture distress. We test this model on a survey-based sample of 177 entrepreneurs in Belgium who either persisted with their distressed venture or started a new one after their distressed venture had failed. Our findings reveal that personal attributes of self-compassion and learning from venture distress can buffer the potential negative effects of venture distress experiences on entrepreneurs' subsequent thriving. In addition, this protective capacity is not mitigated by the failure of the distressed venture. We further discuss the theoretical and practical implications of these findings.
Keywords: L26; M13; I31; 650; Entrepreneurs' well-being; thriving; self-compassion; learning from venture distress; self-determination theory